Non-Financial Performance Measurement for Shariah Banks : A Survey to Masyarakat Ekonomi Syariah (MES) Surakarta - Astuti, Septin Puji; Astika, Hari (SBM ITB, 2011)
Measurement of non-financial performance in shariah banks is needed to enhance their market share and to maintain their long-term sustainability. The main aim of this research is to show the position of shariah banks in Surakarta in respect with their non-financial aspects (i.e. product, service, human resource and image) based on opinions given by members of Shariah Economic Society (MES) of Surakarta. Extent analysis for Fuzzy Analytic Hierarchy Process is employed to measure the non-financial performance of the banks. The result indicates that the first two banks with best non-financial performance are BMI and BSMKeywords: Â Shariah bank, extent analysis, fuzzy analytic hierarchy process, service performanc